Special Supplement: Global Neuro-Oncology - Syed Ather Enam; Hafiza Fatima Aziz; Kaynat Siddiqui; Mohammad Hamza Bajwa; Faiza Urooj; Saqib Kamran Bakhshi; Ahsan Ali Khan; Kee B Park; Tariq Khan (Journal of the Pakistan Medical Association)
In this special supplement of the Journal of PakistanMedical Association, titled "Global Neuro-Oncology(GNO)," we expand upon the Pakistan Brain TumourEpidemiological Study's (PBTES) foundational work.1 Thisedition is dedicated to addressing the critical challengesin global neuro-oncology, with roots in global oncologyand global surgery, as emphasized in leading publicationslike The Lancet.2 It highlights the urgency of tackling braintumours, the 10th leading cause of mortality worldwide,with a particular focus on low- and middle-incomecountries (LMICs) where healthcare disparities are most acute.